How Indomie Survived and Led in the Middle East - Amarudin Daulay (Sultan Publisher, 2024)
The factors contributing to the thriving market penetration of the Indomie brand in the Middle Eastern instant noodle industry. Through an analysis of the brand's localization, affordability, adaptability to dietary needs, marketing, and distribution strategies, the abstract highlights the critical components of Indomie's triumph. The brand's ability to tailor flavors, packaging, and promotional efforts to align with Middle Eastern preferences has played a significant role in its widespread popularity. Moreover, the affordability and accessibility of Indomie products have positioned them as a favored choice across various consumer segments. The brand's recognition and response to dietary considerations, such as halal certification, further underscore its resonance with the regional market. The abstract underscores the insights that can be gleaned from Indomie's success story, particularly in effectively navigating diverse cultural and economic landscapes through strategic alignment and marketing acumen.